PERIMBANGAN PAJAK FISKAL ANTARA PUSAT DAN DAERAH - Anwar, Khairil (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Even though there are regulations regarding the balance between the center and the regions, in practice the fiscal tax balance between the center and the regions is very difficult to implement because various provisions are hampered, especially because of the provisions regulated by the ministry of finance which causes regions to be unable to receive taxes to the fullest and only receive the part that very limited even though the area is rich, the region cannot enjoy its wealth. The solution should be considered considering that regional independence is the main pillar of the Indonesia state, if the region can prosper with a wide income, in turn the country as a whole is going to prosper, but if the region only hopes for general allocation funds and special allocations or the distribution of small gifts from the central government, in turn It also causes the country's progress to stagnate.